Isomerization of alkyl naphthalene and refining of 2-methylnaphthalene - Sun, Hao; Shi, Saijian; Gu, Zhenggui (Chinese journal of chemical engineering, 2017)
A preparation process of 2-methylnaphthalene （2-MN） was proposed by isomerization, side-stream distillation and extractive distillation. The isomerization of alkyl naphthalene was catalyzed by acid-treated HBEA zeolites, and the 2-MN selectivity of isomerization was 92.70%. Side-stream distillation and extractive distillation were investigated by simulation, and effects of operation parameters on 2-MN were studied. Further, the simulated results were verified by experiment. Under the optimal condition, the mass fraction of 2-MN reached to 98.09%; in the oroduct, and the yield was 83.84% in refining orocess.